2005
DOI: 10.4103/0028-3886.16406
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of the middle cerebral artery

Abstract: Although the microsurgical anatomy of the MCA in Indian population correlated with the findings in the western literature, some structural and statistical variations were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 3 publications
12
37
2
1
Order By: Relevance
“…Some of the cortical branches maybe absent and the adjacent branches may share the blood flow. [21] Our study of insular segment of middle cerebral artery differs from other studies mainly in the pattern of division of main trunk into secondary trunks and in variations in origin of cortical branches from secondary trunks. Though trifurcation and even tetrafurcation is reported earlier in many studies, not a single case of true trifurcation was found in our study.…”
Section: Branchcontrasting
confidence: 61%
“…Some of the cortical branches maybe absent and the adjacent branches may share the blood flow. [21] Our study of insular segment of middle cerebral artery differs from other studies mainly in the pattern of division of main trunk into secondary trunks and in variations in origin of cortical branches from secondary trunks. Though trifurcation and even tetrafurcation is reported earlier in many studies, not a single case of true trifurcation was found in our study.…”
Section: Branchcontrasting
confidence: 61%
“…It can be considered the terminal branch of the ICA 7. During the first weeks of fetal life, when the embryo is 7–12 mm long, lateral striate arteries arise from its wall and provide blood supply to embryonic structures of the telencephalic vesicle that eventually become the MCA territory.…”
Section: Review Of Anatomy and Embryologymentioning
confidence: 99%
“…These perforators may arise as multiple single small vessels from the parent artery or from a common larger trunk or take over each other's territory. The MCA typically gives rise to the medial and lateral lenticulostriate artery groups 7 9. These groups can be interconnected and form a rete (the most prominent example of which is the fenestration of the M1).…”
Section: Review Of Anatomy and Embryologymentioning
confidence: 99%
“…Microanatomic studies showed that the variation in length of the M1 segment alone is between 12 and 20 mm and 3–11 lenticulostriate vessels arise along the course of the M1 segment, while the M2 segment is even longer 11. In the aforementioned trials, patients with an M1 and M2 occlusion were included.…”
Section: Introductionmentioning
confidence: 99%